Nanomaterial-based surface-enhanced Raman scattering spectroscopy for sensing and diagnostics of gas molecules in environment and healthcare. Issue 6 (26th September 2022) - Prakash, Jai; de Oliveira, Paulo Roberto; Swart, H. C.; Rumyantseva, Marina; Packirisamy, M.; Janegitz, Bruno C.; Li, Xiaogan
Abstract : The detection and identification of molecular traces in the environment as well as in the human breath are very significant for the development of a healthy society. Abstract : The detection and identification of molecular traces in the environment as well as in the human breath are very significant for the development of a healthy society. This is extremely important from the environmental control and medical diagnostics point of view. A great deal of research is being conducted in the field of gas sensing using a variety of sensing techniques. Even though several sensing materials with low cost have been developed for sensing toxic gases with relatively high sensitivity, however, sensors suffer from certain drawbacks such as poor sensitivity at room temperature. Another fact is that traditional sensors fail to discriminate the signals of different target molecules in the case of multiplex gases. Therefore, developing a sensing tool with high sensitivity, good selectivity, and simple operation for gas detection is of great significance to environment monitoring/protection and human healthcare. In this context, the surface-enhanced Raman spectroscopy (SERS) technique has emerged as one of the promising surface sensitive techniques for the ultra-detection of various kinds of species, such as chemical and biological molecules, including environmental gaseous pollutants. SERS not only provides ultrasensitive detection of molecules but also provides fingerprints of individual gases out of the mixtures, which are very complicated in the case of traditional methods. Recent advances in the SERS technique in sensing toxic and harmful environmental gases are highlighted. Additionally, this technique has shown promising application as a gas biomarker in the human breath to detect related diseases in the human body, which has also been discussed along with its possible application in the detection of SARS-CoV-2 in the breath of COVID-19 patients. Furthermore, challenges in the application of SERS technology for gas detection in the environment and their practical implementations in air pollution control, as well as human healthcare, are addressed.